PENERAPAN MODEL PEMBELAJARAN KOOPERATIF PENDEKATAN STRUKTURAL THINK PAIR SQUARE (TPS) UNTUK MENINGKATKAN HASIL BELAJAR MATEMATIKA SISWAKELAS VIII4 SMP NEGERI 21 PEKANBARU - Yelpi, Rosita; Roza, Yenita; Zulkarnain, Zulkarnain (Jurnal Online Mahasiswa (JOM) Bidang Keguruan dan Ilmu Pendidikan, 2014)
Abstract:This reseacrh based on the students math ability class VIII4 of SMPN 21 Pekanbaru under Minimum Mastery Criteria with a percentage of 38,24% and the learning process still teacher center. The research was classroom action research. This research aims to improve learning process and outcomes students by implementing cooperative learning model structural approach of Think Pair Square. The subject of the research is students of class VIII4 of SMPN 21 Pekanbaru in the first semester academic years 2013/2014. There are 34 students in the class, consisting 19 girls and 15 boys. The instrument of data collection on this research are observation sheets and math achievement tests. The observation sheets are analyze in qualitative descriptive way, while the math achievement tests are analyze in quantitative descriptive way. The qualitative analysis showed an improvement of learning process prior to the action of the first cycle to the second cycle. Then the result of this research showed an increase in students from the base score with the percentage 38,24% to 61,76% on the first daily test and 70,59% on the second daily test. From the results of this study concluded that Cooperative Learning model structural approach of Think Pair Square can improve the students’ learning achievement at class VIII4 of SMPN 21 Pekanbaru in the first semester academic years 2013/2014.Key Word : Mathematics Learning Outcome, Cooperative Learning Model Structural Approach of Think Pair Square, Class Action Research